PENGARUH TAX AMNESTY DAN TARIF PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Bani Binekas; Rendi Kusuma Natita (JURNAL ILMIAH EDUNOMIKA, 2024)
This study measures the influence of tax amnesty and tax rates on taxpayer compliance with the aim of providing further understanding to those implementing tax amnesty programs and setting tax rates. The indicators used to measure taxpayer compliance include timely submission of tax returns; no tax arrears for any type of tax, except for tax arrears that have been approved for installment payments or deferred tax payments; financial statements audited by a public accountant or government financial supervisory agency with an unqualified opinion for three consecutive years; and no convictions for tax-related crimes based on a final court decision within the last five years. The indicators for tax amnesty include taxpayer knowledge of the tax amnesty program, taxpayer understanding of the tax amnesty program, taxpayer awareness of the tax amnesty, and the benefits of the tax amnesty program for taxpayers. The indicators for the tax rate variable include proportional rates, fixed rates, progressive rates, and regressive rates. This research aims to test hypotheses, typically explaining the nature of certain relationships or determining the independence of two or more factors in a situation. This study employs an explanatory method, wherein the researcher seeks to identify the causes of one or more issues. The results of the study indicate that taxpayer compliance is influenced by tax amnesty.